Effects of heat treatment on surface integrity and wear performance of Inconel 718 alloy fabricated by laser powder bed fusion process additive manufacturing under different laser power and scanning speed parameters - KAYNAK, YUSUF (My University, 2023)
As with all additive manufacturing processes, selecting appropriate process parameters in the laser powder bed fusion (LPBF) process plays an important role in the surface integrity and mechanical behavior of Inconel 718 components. Hatch distance, laser power, laser scanning speed and layer thickness are the main parameters that can be altered in the LPBF process. This study focuses on the role of laser power and scanning speed when hatch distance is larger than laser spot size on product properties. This work reveals that LPBF process parameters signifcantly impact the fabricated Inconel 718 material properties. However, although the material properties are enhanced by selecting appropriate process parameters, the components need post-processing methods to have the desired properties. Heat treatment was applied as a post-process to obtain parts with the desired material properties. The efect of heat treatment applied to the parts fabricated at various laser power and laser scanning speeds on the parts’ surface integrity, and mechanical performance is comprehensively presented. Determining the details of the interactions of diferent production parameters with heat treatment is one of the motivations of this study. The presented results establish that heat treatment can change specimens’ microstructural aspects. The results also show a 10% increase in microhardness and a 14% increase in wear performance of specimens, due to the fnal state of the microstructure after heat treatment. Keywords Additive manufacturing · Surface integrity · Laser powder bed fusion · Inconel 718 · Heat treatment
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Havacılık ve Uzay Mühendisliği; Matematik; Bilgisayar Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Aeronautical and Space Engineering; Mathematics; Computer Science; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, MEKANİK; MATEMATİK, UYGULAMALI; MÜHENDİSLİK, İMALAT; MÜHENDİSLİK, HAVACILIK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATHEMATICS; ENGINEERING, MECHANICAL; MATHEMATICS, APPLIED; ENGINEERING, MANUFACTURING; ENGINEERING, AEROSPACE; Otomotiv Mühendisliği; Fizik Bilimleri; Uzay Mühendisliği; Genel Mühendislik; Makine Mühendisliği; Endüstri ve İmalat Mühendisliği; Uygulamalı matematik; Automotive Engineering; Physical Sciences; Aerospace Engineering; General Engineering; Mechanical Engineering; Industrial and Manufacturing Engineering; Applied Mathematics; Additive manufacturing; Heat treatment; Inconel 718; Laser powder bed fusion; Surface integrity